Assessing head and trunk symmetry during sleep using tri-axial accelerometers. (26th November 2013) - Sato, Haruhiko; Ikura, Daiki; Tsunoda, Masahiro
Abstract: Using two types of small, lightweight tri-axial accelerometers, we obtained evidence for the effectiveness of an approach for assessing head–trunk symmetrical or asymmetrical positions during sleep. First, we assessed the accuracy of our monitoring system in five healthy young adults (age range, 22–24 years). The participants wore acceleration monitors on the sternum and forehead; then spent 5 min in six different positions. Once accuracy was confirmed, we assessed head–trunk symmetry during night-time sleep in 10 healthy children (age range, 3–13 years) and 10 young adults (age range, 21–26 years) in their home environments. All participants wore the monitors during one night's sleep in their homes. After computing head–trunk positions using the orientation data obtained by the accelerometers, head and trunk symmetry were evaluated. The head and trunk positions were correctly detected: the positional data from the trunk had 99% agreement, and the data from the head had 96% agreement. Both the young adults and children were observed to spend time with the head–trunk in asymmetric positions; however, the subjects changed position frequently so the asymmetrical postures were mobile. We concluded that the proposed monitoring system is a reliable and valid approach for assessing head–trunk symmetry during sleep at home. Implications for Rehabilitation: We propose a head and trunk symmetry monitoring system using accelerometers. The proposed system could accurately identify head and trunk position. Asymmetrical positioning was seen in healthy participants but it was not immobile.